Assessment of antimicrobial activity in Diplostephium phylicoides and Diplostephium revolutum extracts by plates and wells method - DEL CARMEN ARIAS PALACIOS, JANETH; PEÑA CARRANZA, LEONARDO; PAOLA TORRES NIÑO, NATALIA; EDUARDO RODRÍGUEZ AGUIRRE, OSCAR (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Abstract. In the present work, the evaluation of the antimicrobial activity of Diplostephium phylicoides and Diplostephium revolutum on different microorganisms was carried out on using bacteria such as Escherichia coli (CMPUJ:034), Staphylococcus aureus (CMPUJ:370), Salmonella typhi (CMPUJ:045) and Pseudomonas aeruginosa (CMPUJ:065), yeasts such as Saccharomyces cerevisiae (CMPUJ:H042) and Candida albicans (CMPUJ:H022), and filamentous fungi such as Penicillium chrysogenum (CMPUJ:H061) and Aspergillus niger (CMPUJ:H002). This assessment was made by the method of plates and wells using extracts from the leaves of the previously mentioned plants. The extracts were made with different solvents, ethanol, ethyl acetate, dichloromethane and petroleum ether. The results showed that the ethyl acetate extract of Diplostephium phylicoides has antimicrobial activity against Staphylococcus aureus and Candida albicans; furthermore, the dichloromethane extract showed an inhibitory effect against Saccharomyces cerevisiae. When comparing the extracts of the two plants, under the evaluated conditions, the extracts presented antimicrobial activity, and the ethyl acetate extract of Diplostephium revolutum the one that showed better activity against all the microorganisms.